2017
DOI: 10.3390/ma10101160
|View full text |Cite
|
Sign up to set email alerts
|

A Microwave Thermostatic Reactor for Processing Liquid Materials Based on a Heat-Exchanger

Abstract: Microwaves have been widely used in the treatment of different materials. However, the existing adjustable power thermostatic reactors cannot be used to analyze materials characteristics under microwave effects. In this paper, a microwave thermostatic chemical reactor for processing liquid materials is proposed, by controlling the velocity of coolant based on PLC (programmable logic controller) in different liquid under different constant electric field intensity. A nonpolar coolant (Polydimethylsiloxane), whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In many chemical plants, microwave thermostatic reactors have replaced existing power-adjustable thermostatic reactors. Yongqiang Zhou et al (Zhou et al 2017) proposed processing liquid materials using microwave thermostatic chemical reactors by controlling the coolant velocity. The paper suggested that the reaction vessel contains liquid for the sample and that the microwave coolant flows through a spiral heat exchanger to control the temperature.…”
Section: System Control With Pid Controllermentioning
confidence: 99%
“…In many chemical plants, microwave thermostatic reactors have replaced existing power-adjustable thermostatic reactors. Yongqiang Zhou et al (Zhou et al 2017) proposed processing liquid materials using microwave thermostatic chemical reactors by controlling the coolant velocity. The paper suggested that the reaction vessel contains liquid for the sample and that the microwave coolant flows through a spiral heat exchanger to control the temperature.…”
Section: System Control With Pid Controllermentioning
confidence: 99%
“…As a result, using physical treatment techniques to properly upgrade these ores is generally difficult. Pyrometallurgical extraction techniques are used to extract nickel from laterite ores, which may yield significant nickel recoveries, to solve this challenge [9][10][11][12][13][14][15][16][17][18][19][20][21]. Furthermore, the laterite mineral will have a significant impact on the reducing roasting process.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al developed a temperature controlling microwave drying system based on a feedback controlling loop, and good stability was reported [17], [18]. In order to keep the heated material at a set temperature, Zhou et al proposed a microwave reactor integrated with a heat-exchanger [19]. However, in the above methods, the heated materials are all placed in the batch reactor.…”
Section: Introductionmentioning
confidence: 99%